Effects of cromakalim on the membrane potassium permeability of frog skeletal muscle in vitro. - Benton, D. C. (1992)
1. The effects of the potassium channel opener, cromakalim, and its active enantiomer, lemakalim, have been investigated in frog skeletal muscle. 2. Cromakalim (30-300 microM) increased 86Rb efflux from muscles loaded with the isotope, hyperpolarized the fibres and reduced membrane resistance. 3. These effects were inhibited by the sulphonylureas, glibenclamide and tolbutamide. The IC50 for glibenclamide inhibition of 86Rb efflux was ca. 8 nM. 4. Phentolamine (300 microM) (which blocks responses to cromakalim in smooth muscle and inhibits ATP-sensitive K+ channels in pancreatic beta-cells) had no effect on the reduction in membrane resistance caused by 100 microM lemakalim. 5. Diazoxide (600 microM) had no effect on 86Rb efflux. 6. The similarities of the K+ channel activated by cromakalim in frog skeletal muscle to the channel acted on in smooth muscle and to the ATP-sensitive K+ channel of beta-cells are discussed.